Clinical measurements to assess women’s mental health: self-report questionnaires in common perinatal mental disorders - Mendes-Ribeiro, Jeronimo (2014)
The use of psychiatric scales in clinical practice is widely known and can be useful as a part of diagnostic evaluations, to identify the presence or absence of a given mental disorder, to monitor treatment progress, and also to quantify and record symptom severity. The perinatal period may be associated with adverse outcomes and may have negative impacts on women’s mental health. Even though only a fewinstruments have been developed especially for this subpopulation, there is growing body of evidence suggesting that close, continued monitoring of symptoms and of the conditions most commonly present in this period via the use of self-report questionnaires may improve decision-making and help indicate specialized treatment as early as possible whenever necessary.